Quale valore ai sacrifici di Israele?: La centralità del rito di Yom Kippur e la costruzione del "capro espiatorio" - Appella, Enzo (Rassegna di teologia, 2025)
The contribution wants to bring to attention what is central in the theological structuring of the Leviticus and, therefore, of the entire Pentateuch, that is, the codification of the complex celebration of Yom Kippur or Day of Atonement (Lv 16,1-34). To understand the sacrificial system of ancient Israel, thus avoiding hasty, trivial, incorrect or even misleading readings, it is necessary to recover the generous dimension of gift and forgiveness inherent in the theological category undoubtedly ambivalent of "sacrifice" and, in this framework, to read the construction of the so-called "scapegoat" as a sign of life for the possibility, granted to all Israel and each of its members, to start again.